2022
DOI: 10.1155/2022/8621103
|View full text |Cite|
|
Sign up to set email alerts
|

Corner Detection of the Computer VR Microscope Image Based on the 3D Reconstruction Algorithm

Abstract: In order to solve the problem of multisolution and ill-formedness of the 3D reconstruction method of a single image (purpose), the author proposes a microscope image segmentation algorithm based on the Harris multiscale corner detection. Separating complex engineering images into several simple basic geometric shapes, rebuild them separately to avoid the ill-conditioned solution problem of directly recovering depth information. In order to improve the registration accuracy of the corner-based image registratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Huang suggested a brand-new coarse to fine corner extractor to accurately and effectively extract corner events. A data association approach with spatial, temporal, and velocity direction restrictions is used to track corner events, and the most recent active corner in the vicinity that satisfies the velocity direction criteria is connected with the newly arriving corner event [7]. For point cloud data processing, Chen et al used density-based clustering with the normal vector of a point cloud (rather than the point cloud itself) to extract the common part for further registration.…”
Section: Introductionmentioning
confidence: 99%
“…Huang suggested a brand-new coarse to fine corner extractor to accurately and effectively extract corner events. A data association approach with spatial, temporal, and velocity direction restrictions is used to track corner events, and the most recent active corner in the vicinity that satisfies the velocity direction criteria is connected with the newly arriving corner event [7]. For point cloud data processing, Chen et al used density-based clustering with the normal vector of a point cloud (rather than the point cloud itself) to extract the common part for further registration.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%